2019
DOI: 10.1007/s13197-019-04046-4
|View full text |Cite
|
Sign up to set email alerts
|

Technological and nutritional characterization of wheat breads added with eggplant flour: dependence on the level of flour and the size of fruit

Abstract: Eggplant (Solanum melongena L.) is the third solanaceous of horticultural importance in the world, after potato and tomato. In the agricultural production of this vegetable, there are post-harvest losses and waste generation. Reduction of these inconveniences can be avoided by obtaining ingredients with high nutritional value for food processing, as breadmaking. Changes in wheat dough and bread quality due to the incorporation of eggplant flour were studied. Different levels (5, 7.5, 10%) of replacement with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Their study also found that the total phenols and flavonoids in bread increased significantly with the level of flaxseed 43 . Similar results about the increase of antioxidant capacity by the addition of flaxseed 43 , 44 and eggplant flour 22 in bread. The predicted model (Equation 17 ) for this response is a significant model with R 2 and Adj-R 2 of 0.98 and 0.96, respectively, and with a non-significant lack of fit (P > 0.05) showing the effectiveness of the model.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Their study also found that the total phenols and flavonoids in bread increased significantly with the level of flaxseed 43 . Similar results about the increase of antioxidant capacity by the addition of flaxseed 43 , 44 and eggplant flour 22 in bread. The predicted model (Equation 17 ) for this response is a significant model with R 2 and Adj-R 2 of 0.98 and 0.96, respectively, and with a non-significant lack of fit (P > 0.05) showing the effectiveness of the model.…”
Section: Resultssupporting
confidence: 72%
“…In this regard, many kinds of research have been conducted on the use of fat mimics such as psyllium mucilage and flaxseed mucilage 4 , modified rice starch 14 in cookies and pumpkin powder 15 , and pureed butter beans 16 in sponge cake, psyllium 17 in gluten-free cookies, inulin, and resistant dextrin 18 in gluten-free biscuit, chia seed mucilage 19 in bread and sponge cakes. Enrichment of products with various flours has been also investigated by many researchers [20][21][22][23][24][25][26][27][28] .…”
mentioning
confidence: 99%
“…Cookies prepared with eggplant flour have high fiber content, which increases water absorption and, consequently yield, once it shows a lower shrinkage [ 5 , 42 ]. However, fibers also make the dough more brittle and hard after baking, raising the product hardness [ 43 , 44 ]. Particularly among children, a hardness raise can be a limiting factor for chewing, once that during the school-age occurs the transition from mixed dentition [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…A large portion of application are to help develop functional food. For example, flour was enhanced with eggplant addition to provide antioxidant capacity ( Valerga et al, 2020 ). Some polyphenols have been used as natural pigments to enrich the color and product image.…”
Section: Introductionmentioning
confidence: 99%